Potato Vine Killing or Desiccation - Lincoln Zotarelli; Steven Sargent; Peter Dittmar; Mildred Makani (EDIS)
Proper tuber maturity at harvest is an important factor in producing high-quality fresh-market potatoes. Tuber maturity is generally recognized as an important determinant of storage ability and cooking quality. Maturation can be artificially induced by killing the potato vines prior to harvest. This will benefit tuber appearance, limit tuber size, and improve tuber release from the vine. This revised 4-page fact sheet describes the importance of tuber maturation, potato vine killing timing and available methods, and how to determine when to vine kill and when to harvest after vine kill. Written by Lincoln Zotarelli, Steven Sargent, Peter Dittmar, and Mildred Makani, and published by the Horticultural Sciences Department, January 2016.